Oil-Abundance and Macroeconomic Performance in the GCC Countries - Maalel, Nabil; Mahmood, Haider (International Journal of Energy Economics and Policy, 2018)
Natural resource abundance and its reliance in terms of exports and national income of any resource-rich country may have positive or negative effect on the macroeconomic performance. This paper tests this issue in case of GCC countries by assuming the two proxies for oil dependency as income-dependence and exports-dependence and by using a period 1980-2016. For that purpose, we utilize the non-linear ARDL of Shin et al. (2014) to verify the possible asymmetrical effects of increasing and decreasing oil-dependency on economic growth. We find that the increasing income-dependence has pleasant effect and decreasing income-dependence has adverse effect on economic growth of most of GCC countries. Further, the increasing exports-dependence has adverse effect and decreasing oil-exports dependence has pleasant effect on economic growth of most of GCC countries. Furthermore, asymmetrical effects of increasing and decreasing oil-dependence on economic growth have been found in most of country cases. Keywords: Oil Dependency; Economic Growth, GCC Countries; non-linear ARDL JEL Classifications: Q26; O47; O57; C52